2022
DOI: 10.2147/ijn.s376358
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Layered PLGA-PEI Nanoparticles Functionalized with TKD Peptide for Targeted Delivery of Pep5 to Breast Tumor Cells and Spheroids

Abstract: Purpose Peptide-based therapy is a promising strategy for cancer treatment because of its low drug resistance. However, the major challenge is their inability to target cancer cells specifically. So, a targeted nano-delivery system that could deliver therapeutic peptides selectively to cancer cells to stimulate their action is highly desirable. This study aims to deliver the antitumor peptide, Pep5, to breast tumor cells selectively using a targeting peptide functionalised multi-layered PLGA-PEI n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…In addition, Mohan et al prepared peptide 5 (Pep5) encapsulated PLGA-PEI nanoparticles. These particles are further modified by TKD to target tumor cells, resulting in a dipeptide-functionalized multilayer nanodrug delivery system (Pep5-TPPN) [ 130 ]. Studies have reported that Pep5 is likely to promote the destruction of tumor cytoskeleton by binding to Plectin or CLIC1.…”
Section: Disturbing Cytoskeleton By Various Nanomaterials For Enhance...mentioning
confidence: 99%
“…In addition, Mohan et al prepared peptide 5 (Pep5) encapsulated PLGA-PEI nanoparticles. These particles are further modified by TKD to target tumor cells, resulting in a dipeptide-functionalized multilayer nanodrug delivery system (Pep5-TPPN) [ 130 ]. Studies have reported that Pep5 is likely to promote the destruction of tumor cytoskeleton by binding to Plectin or CLIC1.…”
Section: Disturbing Cytoskeleton By Various Nanomaterials For Enhance...mentioning
confidence: 99%